(untitled) (Research, Society and Development, 2021)
Objective: To demonstrate the choice of the mode of delivery from the perspective of women’s autonomy. Method: This is an integrative literature review performed in Medical Literature Analysis and Retrieval System Online (MEDLINE), Database in Nursing (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), with a time frame of the last 5 years in Portuguese, English and Spanish and had as exclusion criteria incomplete articles, repeated in the databases and that escaped the theme. Result and Discussion: Prenatal care is the first step towards childbirth and, therefore, it is in it that all the pregnant women’s doubts and fears should be discussed. It should be noted that childbirth is a natural and physiological process that, normally, when properly conducted, does not need interventionist conduct. The pregnant woman’s cultural values, feelings and needs should also be discussed. The parturient should be informed and oriented about the evolution of labor, remembering and recognizing the main role of women in this process, even accepting their refusal to conduct that cause them embarrassment or pain. Conclusion: This study only sought to conduct a prior discussion of the importance of knowledge of pregnant women about the risks of the mode of delivery to which they will be submitted and to analyze their preferences about the procedures used for the birth of the baby, thus allowing us to collect information to legitimize both the options for the route of delivery.